Automatic Production of [18F]F-DOPA Using the Raytest SynChrom R&D Module - Paweł Waśniowski; Jolanta Czuczejko; Michał Chuchra; Mateusz Wędrowski; Dawid Marciniak; Stanisław Sobiak; Bogdan Małkowski (MDPI AG, 2022)
[18F]F-DOPA is widely used in PET diagnostics. Diseases diagnosed with this tracer are schizophrenia, Parkinson's disease, gliomas, neuroendocrine tumors, pheochromocytomas, and pancreatic adenocarcinoma. It should be noted that the [18F]F-DOPA tracer has been known for over 30 years. However, the methods of radiosynthesis applied in the past did not allow its clinical use due to low efficiency and purity. Currently, in the market, one encounters different types of radiosynthesis using the fluorine 18F isotope and variants of the same method. The synthesis and its modifications were carried out using a Raytest Synchrom R&D module. The synthesis consists of the following steps: (a) binding of the fluoride anion 18F− on an anion exchange column; (b) elution with TBAHCO3−; (c) nucleophilic fluorination to the ABX 1336 precursor; (d) purification of the intermediate product on the C18ec column; (e) Baeyer-Villiger oxidation; (f) hydrolysis; and (gfinal purification of the crude product on a semipreparative column. The nucleophilic synthesis of [18F]F-DOPA was successfully performed in 120 min, using the ABX 1336 precursor on the Raytest SynChrom R&D module, with a radiochemical yield (RCY) of 15%, radiochemical purity (RCP) ≥ 97%, and enantiomeric purity (ee) ≥ 96%.